2020
DOI: 10.1093/jac/dkaa063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic analysis of an XDR Pseudomonas aeruginosa ST664 clone carrying multiple conjugal plasmids

Abstract: Objectives A group of ST664 XDR Pseudomonas aeruginosa strains have been isolated from a burn clinic. Here we decipher their resistomes and likely mechanisms of resistance acquisition. Methods The complete nucleotide sequences of representative isolates were determined, by PacBio and Illumina MiSeq sequencing, and analysed for antimicrobial resistance (AMR) genes as well as sequence variations. S1-PFGE was used to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…No alterations were detected in AmpDh2, while mutation A219T in AmpDh3 was identified in all the isolates. This amino acid change in AmpDh3 was described before in multidrug-resistant P. aeruginosa isolates from ST175 and ST664 [ 36 , 37 ]. No mutations in the AmpC regulator dacB (PBP4) were found in our isolates.…”
Section: Resultsmentioning
confidence: 56%
“…No alterations were detected in AmpDh2, while mutation A219T in AmpDh3 was identified in all the isolates. This amino acid change in AmpDh3 was described before in multidrug-resistant P. aeruginosa isolates from ST175 and ST664 [ 36 , 37 ]. No mutations in the AmpC regulator dacB (PBP4) were found in our isolates.…”
Section: Resultsmentioning
confidence: 56%
“…Members of this family displayed a size of 300-500 Kb and several AMR genes. However, those carrying bla KPC-2 genes were only reported in China [18, 59]. The current study showed that this megaplasmid spread widely around the country as we identified the plasmid in Eastern and Central China.…”
Section: Discussionmentioning
confidence: 60%
“…This suggested that this mobile genetic element (MGE) carrying bla KPC-2 might be able to transfer between two plasmid types, especially in case of ZPPH8 which contained both plasmids. The Type 2 plasmid containing the genetic context in which the bla KPC-2 was embedded, had been recently reported in Tianjin, China [18]. Interestingly, a sequence alignment showed that plasmid pNK546-KPC underwent large segment inversion next to the bla KPC-2 region (Figure 5).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations